Automated tools to implement and test Internet systems in reconfigurable hardware. - Lockwood, John W. (Computer communication review.)
Tools have been developed to automatically integrate and test networking systems in reconfigurable hardware. These tools dynamically generate circuits for Field Programmable Gate Arrays (FPGAs). A library of hardware-accelerated modules has been developed that processes Internet Protocol (IP) packets, performs header rule matching, scans pocket payloads, and implements per-flow queueing. Other functions can be added to the library as extensible modules.An integration tool was developed to enable a network administrator to specify how a customized system should examine, drop, buffer, and/or modify packets. This tool joins together modules from the library to create a composite circuit that performs multiple functions. The tool allows additional modules to be quickly added to the library and integrated into systems. The integration tool has been used to create circuits that perform Internet firewall, network intrusion detection, network intrusion prevention, and Denial of Service (DoS) attack protection functions.A test tool was developed to automatically verify that circuits created by the integration tool run properly in reconfigurable hardware. Circuits created by the integration tool are deployed into a Field-programmable Port Extender (FPX) platform. As new modules were added to the library, the test tool reconfigured the logic on the FPX, injected traffic, and monitored the resulting packets.By using hardware, not software, networking system can process millions of packets per second. Together, the integration and test tools simplify the otherwise difficult task of developing reconfigurable hardware for networking systems and testing them at Gigabit per second rates.